Lipid Oxidation Assessed by Indirect Calorimetry Predicts Metabolic Syndrome and Type 2 Diabetes - Pujia, Arturo; Mazza, Elisa; Ferro, Yvelise; Gazzaruso, Carmine; Coppola, Adriana; Doldo, Patrizia; Grembiale, Rosa Daniela; Pujia, Roberta; Romeo, Stefano; Montalcini, Tiziana (Frontiers in Endocrinology, 2019)
Purpose: Diabetes has been linked to an impaired ability to oxidize fatty acids. Fat oxidation can be assessed clinically by a respiratory quotient measurement during fasting. We hypothesised that a respiratory quotient might predict metabolic syndrome and type 2 diabetes onset. Methods: In this longitudinal study we used an existing database of 233 individuals who had complete nutritional and biochemical data at baseline and after 12-month follow-up. All participants underwent an indirect calorimetry to measure the respiratory quotient. We excluded participants with diabetes, metabolic syndrome, chronic diseases and those who had changed food habits in the previous three months. Only 88 subjects met the inclusion criteria. Results: Two individuals developed type 2 diabetes and 10 metabolic syndrome after one year. Participants in the high respiratory quotient group (>0.91) had a higher incidence of metabolic syndrome/diabetes than those in the low quotient group (25% vs 8% p=0.04). In this group, mean basal respiratory quotient was 0.97 ± 0.04. In the high respiratory quotient group, Kaplan-Meier curves showed a greater probability of having metabolic syndrome/diabetes than those in the low respiratoryquotient group (log Rank χ2 test = 8.44; p = 0.004). A multivariable Cox proportional hazards model demonstrated that energy expenditure and weight increase did not predict metabolic syndrome/diabetes [HR (95% CI) = 1 (0.996-1.005), p =0.86 and 3.9 (0.407-38.061), p=0.23 respectively). Conclusions: A greater probability of metabolic syndrome/diabetes was found in individuals with a basal respiratory quotient of >0.91 than in those with a respiratoryquotient of ≤0.91 after 1 year. In the short-term anthropometric measurements and their variation overtime were not correlated with metabolic syndrome/diabetes.